Rancang Bangun Model Alat Uji Teras Reaktor Nuklir Small Modular Reactor (SMR) Dengan Fluida Pendingin H2O Untuk Kondisi Konveksi Paksa - Ramadhan, Anwar Ilmar; Dermawan, Erwin; Diniardi, Ery; Arifangga, Muhammad (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2015)
Heat transfer performance poor will have a negative impact on the reactor system which in turn could affect the release of radioactive substances into the surrounding environment so as to endanger the safety of the environment and living things that exist around the reactor. The purpose of this research is to create or design a testing tool wake models in a nuclear reactor core in a laboratory scale assuming cylindrical heat derived from the electrical energy that does not harm the environment. The method used in the completion design of the reactor core model of test equipment is the study of literature, making the concept design and subsequent testing tool designing wake. Once the design is complete, the next stage of the operation of test equipment to determine the performance of the test equipment. The comparison between experimental simulation on the condition of forced convection heat flux 500000 W/m2 at a speed of 0.3 m/s produces fluid temperature difference between 0.00001 K to 0.8 K. In natural convection comparison between experimental results with simulation the heat flux 500000 W/m2 at a speed of 0.3 m/s resulted in the difference between the 0.1 K to 28 K. The smaller the fluid temperature differences between the experimental simulations, the better the performance of the test equipment.